ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA HASIL TENAGA PENJUALAN DAN HUBUNGANNYA TERHADAP EFEKTIFITAS PENJUALAN PERUSAHAAN ( STUDI KASUS PADA BPR DI EKS. KARESIDENAN SEMARANG) - Kusmanto Kusmanto; Joko Sampurno (JURNAL STUDI MANAJEMEN ORGANISASI, 2012)
ABSTRACT Sales force has very important role in life of banking in reaching its target. A good Management of sales force has important influence to reach effectiveness sale of company. Meanwhile, previous research mention that it is important to examine some performance of sales force factors with selling growth. This research hypothesized performance of sales force tactors influence to the effectiveness of selling of company. According to the literary review about sales force control system, the strenght of sales force, trust to wards the sales force influence the result performance of sales force and its relation with effectiveness sale of company this research propose four hypothesis, they are: H1-the sales force control systems have an positive effect on to performance result of sales force, H2-sales force reliability have an positive effect on to trust to sales force, H3-the trust at sales force have an positive effect on performance result of sales force, H4-performance result of sales force have an positive effect on effectiveness sale of company. To test the hypothesis research uses 105 questionnaires in this study. The population in this research sales force at Bank Perkreditan Rakyat (BPR) in eks. Karesidenan Semarang. The datas is then analysed by means of SEM of AMOS to test the causality relation of hypothesis. From result of the analysis have fulfilled Criteria Goodness-of-Fit. Chi-Square (107.203). Probability (0.052), RMSEA (0.050), CMIN/DF (1.262), TLI (0.955), and CFI (0.963) so that can be told this model competent to be used. Examination of raised hypothesis indicate that hypothesis 1,2,3, and 4 have up to standard which determined that is value of CR > 2.00 with the SEM propose theoretical implication that result performance of sales force can have implication on effectiveness sale of company. This reseach also propose implication of managerial is that factors variable which influence the result performance of sales force and its relationship with selling effectiveness of company is positively increasing the result performance of sales force trough sales force ability which is had by Bank Perkreditan Rakyat (BPR). There are several implications for future research about performance of sales force bul location and object different so that equal can result. Keywords :  The sales force control systems; sales force reliability; the trust at sales force; performance result of sales force; and effectiveness sale of company